Comparative Structure–Activity Analysis of the Antimicrobial Activity, Cytotoxicity, and Mechanism of Action of the Fungal Cyclohexadepsipeptides Enniatins and Beauvericin - Hamza Olleik; Cendrine Nicoletti; Mickael Lafond; Elise Courvoisier-Dezord; Peiwen Xue; Akram Hijazi; Elias Baydoun; Josette Perrier; Marc Maresca (Toxins, 2019)
Filamentous fungi, although producing noxious molecules such as mycotoxins, have been used to produce numerous drugs active against human diseases such as paclitaxel, statins, and penicillin, saving millions of human lives. Cyclodepsipeptides are fungal molecules with potentially adverse and positive effects. Although these peptides are not novel, comparative studies of their antimicrobial activity, toxicity, and mechanism of action are still to be identified. In this study, the fungal cyclohexadepsipeptides enniatin (ENN) and beauvericin (BEA) were assessed to determine their antimicrobial activity and cytotoxicity against human cells. Results showed that these peptides were active against Gram-positive bacteria, Mycobacterium, and fungi, but not against Gram-negative bacteria. ENN and BEA had a limited hemolytic effect, yet were found to be toxic at low doses to nucleated human cells. Both peptides also interacted with bacterial lipids, causing low to no membrane permeabilization, but induced membrane depolarization and inhibition of macromolecules synthesis. The structure−activity analysis showed that the chemical nature of the side chains present on ENN and BEA (either iso-propyl, sec-butyl, or phenylmethyl) impacts their interaction with lipids, antimicrobial action, and toxicity.